FAKTOR-FAKTOR YANG DIPERTIMBANGKAN KONSUMEN DALAM MEMILIH MINIMARKET - Dadi Akhmad Perdana; Putu Rani Susanthi (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
The competition of retail shop, especially mini-markets, is currently getting tougher, and more mini-markets were in almost all cities in Indonesia. The strategy of Minimarket to growth up was they were carry a franchise strategy to increase the number of branches they have. The success in increasing the number of branches significantly has made Minimarkets a favorite place for shopping, replacing the roles that previously carried out by warungs/little shops and traditional markets. However, along with the rapid growth of the minimarket, the competition among the minimarket businesses is becoming increasingly tight, so they are trying hard to carry out the right marketing strategy. And to implement the right marketing strategy, first they need to know what factors are considered by consumers to choose the right minimarket to shop and then apply it in their marketing strategy